The Effect of Students’ Perception on Educational Tourism and Self-Fulfilment - Reza Fahmi; Furkan Besel; Prima Aswirna; Farah Audi Fahmi; Danial Muhammad Fahmi (Cendekia: Kependidikan dan Kemasyarakatan, 2021)
Abstract: Educational tourism can be built as a bridge between society and the Islamic Boarding School. It’s also can improve a new entrepreneurship model in Islamic Boarding School. The study used a quantitative approach. The population was about 387 students who were involved as a population in the study. But only 196 people as a sample. The sampling technique is simple random sampling. The data collection technique was the psychology scale—data analysis technique with a Pearson correlation statistical model. This study found that: (1) the distribution of mean and percentage of educational tourism perception had not been developed or low; (2) the distribution of min and portion of self-fulfillment of students was high; (3) there was an effect between students' perception about education tourism and their self-fulfillment. Abstrak: Wisata edukasi dapat menjadi jembatan antara masyarakat  dan pondok pesantren yang tidak mengetahui tentang pondok pesantren. Pengembangan pariwisata pesantren memberi ruang terbentuknya kewirausahaan baru di pesantren. Penelitian menggunakan pendekatan kuantitatif. Populasi sebanyak 387 siswa yang dilibatkan sebagai populasi dalam penelitian. Tapi hanya 196 orang sebagai sampel. Teknik pengambilan sampel dengan simple random sampling. Teknik pengumpulan data menggunakan skala psikologi. Teknik analisis data dengan model statistik regresi sederhana. Hasil penelitian ini menemukan: (1) sebaran rerata dan persentase persepsi tentang wisata pendidikan belum berkembang atau rendah. (2) sebaran min dan persentase pemenuhan diri siswa tinggi. (3) ada pengaruh antara persepsi siswa tentang wisata pendidikan dengan kemandirian santri.